Training program for community health workers in remote areas in Senegal, first experience - Sarli, L.; Enongene, E.; Bulgarelli et al., K. (Acta Biomedica Atenei Parmensis, 2010)
Background: In some countries, community health workers (CHWs) act as a bridge between the health care delivery system and the community, and ensure primary health care. It is essential to improve health worker education and training; however, in remote areas such as rural Senegal villages, these CHWs are often unable to leave their home community for training and education. We set out to perform a training program in a village in Senegal and to evaluate its effectiveness in that village. Methods: We prepared a training program to be based on face-to-face lessons and practical exercises; a nurse from the university of Parma carried out the training of the CHW in loco for a period of four weeks. After six months, the nurse with an anthropologist returned to the village to verify the results of the training program. Results: The CHW had retained most of what she had been taught, but her opinion about the training program was not altogether positive, given that the absence of a working health centre in the village and an insufficient period of practical experience in a hospital. The village community did not understand the role of the CHW and was not informed that there was a training program to help increase her technical know-how. Conclusions: This experience confirmed the important role of the CHW in rural areas in a poor region in Senegal, in the absence of other professional healthcare figures readily accessible to the population. Nonetheless, in order to properly carry out the role of CHWs, an adequate theoretical and practical training is necessary.